A modified rat model of 8 minutes asphyxial cardiac arrest and cardiopulmonary resuscitation - Xin Liu; Yan Li; Yinghua Gu; Fa Wang; Biyun Tian; Wenxun Liu; Qingshan Ye (PLoS ONE, 2025)
The animal model of cardiac arrest (CA) and cardiopulmonary resuscitation (CPR) serves as a crucial tool for investigating the pathophysiology and treatment strategies associated with cardiac arrest, however, standardized procedures for such models remain insufficiently established. We aimed to modify and specify the existing rat model of asphyxial CA and CPR while providing an analysis of long-term outcomes.A total of 46 rats were allocated into two groups,sham and CA group.In CA group, cardiac arrest was induced through 8 minutes of hypoxia prior to the administration of CPR. In sham group, only tracheal intubation and vascular catheterization were conducted under isoflurane anesthesia. Key parameters along with arterial blood gas results during modeling were meticulously recorded. After a 2-week postoperative observation period, the survival rate of rats and neurobehavioral changes on days 1, 3, 7, and 14 following resuscitation were assessed. Two weeks later, a pathological examination of brain tissue was conducted to evaluate neuronal damage. Results indicated that the average duration of cardiac arrest in CA group was 292.9 ± 12.5 seconds, with a return of spontaneous circulation rate of 78.95% and a survival rate at day 14 reaching 32%. After a duration of 2 weeks, the neurobehavioral scores of the surviving rats returned to their initial baseline levels; however, pathological examination revealed evidence of neuronal damage. In conclusion, we present a refined protocol for establishing a stable rat model of asphyxial CA and CPR, which may assist researchers in this field in enhancing the success rate of modeling.